The Transmission of Irish Law in the Fourteenth and Sixteenth Centuries: Exploring the Social and Historical Contexts - Hallinan, Maria (Studia Celtica Posnaniensia, 2019)
This paper seeks to examine the contexts in which the Old Irish law tracts were transmitted in the period following the church reforms and Anglo-Norman invasion of the twelfth century, focusing primarily on the fourteenth and sixteenth centuries. Within these time frames two major themes will be appraised: 1) the English attitudes towards the practice of Irish law, and 2) the roles of the medieval lawyers and/or their patrons in political life. The central aim of this paper is twofold; firstly to shed light on the historical and social contexts in which the legal materials were later transmitted, and secondly, based on this, to posit some theories as to the possible incentives behind the transmission of the law tracts in these periods.